LEGAL PROTECTION AGAINST CHILDREN VICTIMS OF SEXUAL VIOLENCE IN THE DIRECTORATE GENERAL CRIMINAL AGENCY-POLDA BALI - Suartana, Komang; Wirya Darma, I Made (Kertha Semaya : Journal Ilmu Hukum, 2020)
This study aims to analyze the legal protection provided for children as a victim of sexual violence at the Bali Regional General Criminal Investigation Directorate and any legal action could be taken if the legal protection for child victims is not implemented. This is an empirical juridical legal study. The results show that the legal protection provided to children as a victim of sexual violence includes the humane treatment of children following the dignity and rights of the child, the provision of special assistants for children from an early age from Social Service Workers and others. The legal action is taken if the legal protection over the child victims is in the investigation stage, the victim feels that he has not received any legal service or protection from the investigator in terms of the rights of the child as a victim and his family can report to his superiors so that the investigator’s performance can be evaluated to provide a maximal legal service and protection for the child.